2022
DOI: 10.3389/fnmol.2022.850904
|View full text |Cite
|
Sign up to set email alerts
|

Translocator Protein Ligand Etifoxine Attenuates MPTP-Induced Neurotoxicity

Abstract: Parkinson’s disease (PD) is a neurodegenerative disease, but the currently available treatments for this disease are symptomatic treatments. There is evidence that translocator protein (18 kDa) (TSPO) expression is upregulated in some neurodegenerative diseases, and TSPO ligands have obvious neuroprotective effects. However, the neuroprotective effects and other potential effects of the TSPO ligand etifoxine in PD remain unclear. Therefore, the present study was designed to explore the impacts of etifoxine on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…A recent research by Tian et al (2022) showed the beneficial effects of etifoxine in a model of neurodegenerative disease, induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). Etifoxine significantly reduced MPTP-induced neurotoxicity and neuroinflammation, motor function disturbances, diminished the production of inflammatory mediators, and infiltration of leukocytes in the brain after MPTP exposure in mice [21]. Our results are also in accordance with the report of Zhang et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…A recent research by Tian et al (2022) showed the beneficial effects of etifoxine in a model of neurodegenerative disease, induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). Etifoxine significantly reduced MPTP-induced neurotoxicity and neuroinflammation, motor function disturbances, diminished the production of inflammatory mediators, and infiltration of leukocytes in the brain after MPTP exposure in mice [21]. Our results are also in accordance with the report of Zhang et al (2020).…”
Section: Discussionmentioning
confidence: 99%